Pengaruh Media Video dan Motivasi Terhadap Hasil Belajar IPA Siswa Kelas V Sekolah Dasar - Vivi M. Ponowu; Richard D. H. Pangkey; Risal M. Merentek (Peneliti.net, 2021)
This study aims to examine whether there is an effect of the use of video media and motivation on natural science learning outcomes of students in the fifth grade of Adventist Elementary School in Maesaan District. This research is a research that uses a quantitative approach with a survey method, which tests the proposed hypothesis by describing and analyzing the interrelationships of the existing variables. The results show that the results of simple regression analysis show the value of Tcount 3.337 > 2,018 T table, then H0 is rejected, so it can be concluded that the video media variable has an effect on the natural science learning outcomes variable, thus accept hypothesis I which states that there is a significant effect of video media on the natural science learning outcomes of students in the fifth grade of Adventist Elementary School, Maesaan District. The results of simple regression analysis show that the value of Tcount is 3.182 > 2,018 T table, then H0 is rejected, so it can be concluded that the variable of student learning motivation affects the variable of learning outcomes of natural sciences, thus accept hypothesis II which states that there is a significant effect of student motivation on learning outcomes of science natural knowledge of students in the fifth grade of the Maesaan District Adventist Elementary School (Y). This shows that motivation has a significant effect on natural science learning outcomes. The results of multiple regression analysis show the value of Fcount = 6.149 > Ftable 3.21 with a significance level of 0.05 and 0.004 < 0.05, so from the results of this data analysis it can be concluded that the multiple regression model has a significant effect jointly between the video media variables and student learning motivation on the results. learn natural sciences, thus accept hypothesis III in this study which states that there is an effect of the use of video media and students' learning motivation on students' natural science learning outcomes in fifth grade Adventist Elementary School, Maesaan District.